Treatments and outcomes of untreated cerebral cavernous malformations in China: study protocol of a nationwide multicentre prospective cohort study - Shufa Zheng; Fuxin Lin; Qiu He; Zhuyu Gao; Lianghong Yu; Dengliang Wang; Yuanxiang Lin; Dezhi Kang (BMJ Open)
Introduction The treatment decision and long-term outcomes of previously untreated cerebral cavernous malformation (U-CCM) are still controversial. Therefore, we are conducting a nationwide multicentre prospective registry study in China to determine the natural history and effect of surgical treatment on long-term outcomes in Chinese people with U-CCM.Methods and analysis This study was started on 1 January 2018 and is currently ongoing. It is a cohort follow-up study across a 5-year period. Patients will be followed up for at least 3 years after inception. Patients with U-CCM will be enrolled from 24 Grade III, level A hospitals distributed all over China. The cohort size is estimated to be 1200 patients. Patients are registered in surgically treated group and conservatively treated group. Clinical characteristics, radiology information and laboratory data are prospectively collected using an electronic case report form through an electronic data capture system. The primary outcome of this study is poor clinical outcome at the last follow-up (modified Rankin Scale score >2 lasting at least 1 year). The secondary outcome includes symptomatic haemorrhage, drug refractory epilepsy, focal neurological deficits, morbidity and all-cause mortality during follow-up. Univariate and multivariate regression analysis will be performed to determine the risk factors for poor outcomes in all patients, and to estimate the effect of surgery. Life tables, Kaplan-Meier estimates, log-rank test and proportional hazards Cox regression will be used to analyse the follow-up data of conservatively treated patients to determine the natural history of U-CCM. Initial presentation and location of U-CCM are prespecified subgroup factors.Ethics and dissemination The study protocol and informed consent form have been reviewed and approved by the Research Ethical Committee of First Affiliated Hospital of Fujian Medical University (FAHFMU-2018-003).Written informed consent will be obtained from each adult participant or from the guardian of each paediatric participant. The final results will be published in peer-reviewed journals.Trial registration number NCT03467295.